2021
DOI: 10.3390/healthcare9091146
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nordic Walking Training on Vitamin D Level in the Blood and Quality of Life among Women Aged 65–74

Abstract: Introduction. Demographic forecasts indicate the progressive aging process of societies in all countries worldwide. The extension of life span may be accompanied by deterioration of its quality resulting from a decrease in physical activity, mental or even social performance, and a deficit in certain chemical compounds responsible for proper functioning of the body. Aim. The aim of the study was to evaluate the influence of a 12-week Nordic walking (NW) training intervention on the level of vitamin D in the bl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Finally, the HRQOL evaluation reveals a great to excellent overall quality of life with sub-scores for mental and physical scores of 74.9 ± 17.3 and 71.9 ± 19.1, respectively. Interestingly, the results suggest a higher overall quality of life among our participants when compared to aged-matched non-exercisers (main physical score of 58 ± 4.6), and similar to what can be observed in regular Nordic walkers aged 65-74 years old (main physical score of 72.1 ± 4.2) [31]. In addition, while the total health self-perception of our participants is found to be similar to what was previously observed among 50 to 65 year-old postmenopausal brisk-walking women [24], it appears to be significantly higher than what has been recently shown among tertiary men and women workers aged 45-55 years old, who reported an overall health perception score between 4.2 and 5.8 out of 10 [32].…”
Section: Discussionsupporting
confidence: 87%
“…Finally, the HRQOL evaluation reveals a great to excellent overall quality of life with sub-scores for mental and physical scores of 74.9 ± 17.3 and 71.9 ± 19.1, respectively. Interestingly, the results suggest a higher overall quality of life among our participants when compared to aged-matched non-exercisers (main physical score of 58 ± 4.6), and similar to what can be observed in regular Nordic walkers aged 65-74 years old (main physical score of 72.1 ± 4.2) [31]. In addition, while the total health self-perception of our participants is found to be similar to what was previously observed among 50 to 65 year-old postmenopausal brisk-walking women [24], it appears to be significantly higher than what has been recently shown among tertiary men and women workers aged 45-55 years old, who reported an overall health perception score between 4.2 and 5.8 out of 10 [32].…”
Section: Discussionsupporting
confidence: 87%
“…For example, Fernandes & Barreto Jr (2017) suggested that physical activity may help to achieve higher vitamin D serum levels in the population, as factors other than sun exposure appeared to be responsible for higher vitamin D levels in more active individuals; however, this phenomenon needs further investigation. In addition, increased vitamin D levels ( p < 0.0001) were identified in women aged 65–74 years after training outdoors in Nordic walking 3 times a week for 60 min, from April to June; no statistically significant changes were found in the control group ( Podsiadło et al, 2021 ). In light of these results, the authors of this study concluded that physical activity of average intensity, carried out outdoors (with sun exposure), positively affected the level of vitamin D; however, taking other studies into account, they concluded that indoor activity (without direct exposure to sunlight) may also have an positive influence.…”
Section: Discussionmentioning
confidence: 91%
“…We identified 946 articles through our database searches and three additional articles were identified through reference list searches. After removing duplicates, the titles and abstracts of 667 articles were screened; 123 full-text articles were assessed for eligibility, 32 were included in the review [ [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] ] and 24 in the meta-analysis [ [22] , [23] , [24] , [25] , [26] , 29 , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [40] , [41] , [42] , [43] , [45] , [46] , [47] , [48] , [49] , 51 ] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In most studies the physical activity interventions were supervised but two home-based physical activity programs were unsupervised [ 26 , 40 ] and two studies had both supervised training sessions and unsupervised home-based sessions [ 39 , 44 ]. Six studies did not clearly state whether the physical activity sessions were supervised or not [ 36 , 38 , [46] , [47] , [48] , 52 ]. The frequency of the physical activity interventions ranged from once a week to once daily, with the length of each session ranging from 30 to 75 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation